Changes in strength and power qualities over two years in volleyball players transitioning from junior to senior national team - Sheppard, J. M.; Nolan, E.; Newton, R. U. (The Journal of Strength and Conditioning Research, 2012)
The purpose of this investigation was to examine the changes in performance indicators as they relate to strength and speed-strength development, over 2 years in a group of volleyball players who successfully transitioned from age group (U21) to senior national team in that time period. Sixteen male subjects (age: 18.5 ± 1.5 years, height: 2.00 ± 0.06 m, and weight: 88.4 ± 7.7 kg) participated in this 2-year longitudinal study. During the 24-month period of this investigation, all the subjects gained professional European contracts and also debuted with at least 1 senior national team match. These included, at a minimum, not only international friendly matches but also senior continental championships, World Championships, and the World Cup. Testing included 1 repetition maximum (1RM) and 3RM for the clean and squat, a maximum effort counter movement vertical jump (CMVJ), depth jump from a 0.35-m box (DJ), spike jump (with approach) (SPJ), and lower body speed-strength assessment with a body weight and body weight + 50% load. Large magnitude increases were observed for CMVJ, DJ, and SPJ over the 2-year period (d = 0.80, 0.82, and 0.94, respectively, p < 0.001). Unloaded (body weight) and loaded jump-squat performance also exhibited large improvements for all measured parameters, with very large increases in jump height in the unloaded (d = 1.21, p = 0.002) and loaded jump squat (d = 1.346, p < 0.001). Very large magnitude changes in 1RM Clean and 3RM Squat (d = 1.56 and 2.21, respectively, p < 0.001) were observed over the 2-year investigation period, and a large increase (d = 1.18, p < 0.001) in the lean mass ratio (mass/sum skinfolds). To progress from junior representation to senior national team, volleyball players must increase their CMVJ and SPJ. This is best accomplished through increasing lean mass, reducing fat mass, improving strength and speed strength, and developing high levels of stretch-load tolerance in stretch-shorten cycle activity.